A new two-level information protection scheme based on visual cryptography and QR code with multiple decryptions. (July 2019) - Fu, Zhengxin; Cheng, Yuqiao; Liu, Sijia; Yu, Bin
Highlights: Two-level protection scheme was designed using visual cryptography and QR code. Public-level information could be read out directly using standard QR code reader. Privacy-level information could be decoded by three different decryptions. The scheme had low computational complexity, robustness and high payload. The experimental results with the scheme supports the theoretical results. Abstract: Nowadays, Quick Response (QR) code has been used in many fields due to its advantages, such as reliability, high-speed scanning and large data capacity. However, embedding the privacy information into the QR code lacks adequate security protection. In this paper, a new two-level information protection scheme is designed based on visual cryptography and QR code. Using any standard QR reader device or software, the public-level information can be read out directly from the shares. Moreover, the privacy-level information can be decoded by three different decryptions, which are suitable to non-computation with relative difference 1/4, lightweight computation with relative difference 1/2 and common computation environments with relative difference 1, respectively. Since the proposed scheme keeps the advantages of visual cryptography and QR code, it differs from the related schemes with low computational complexity, robustness against deformations, and high payload. The effectiveness of the proposed scheme has been proved theoretically. Experimental results and analysis demonstrate that the proposed scheme can protect two-level information with multiple decryptions, and has many benefits compared with the previous schemes.